The Effect of Multi-Strain Probiotic on the Metabolic Activity of the Intestinal Microflora in Infants with Functional Disorders of the Gastrointestinal Tract: the Results of a Placebo-Controlled Study - I. N. Zakharova; M. D. Ardatskaya; N. G. Sugyan ("Paediatrician" Publishers LLC, 2016)
Background: Probiotics are widely used in pediatrics for correcting the intestinal microflora. However, the recovery of metabolic activity of the obligate intestinal microflora has vital importance.Objective: Our aim was to study clinical efficacy of a multi-strain probiotic in functional disorders of the gastrointestinal tract (GIT) and its effect on the metabolic activity of the intestinal microflora in infants.Methods: The comparative placebo-controlled study included children aged from 2 weeks to 6 months with functional GIT disorders. The duration of follow-up was 21 days. We analyzed the dynamics of symptoms of functional GIT disorders, as well as indices of the metabolic activity of the intestinal microflora on the basis of GLC results of fecal samples.Results: The main group (received multi-strain probiotic) comprised 30 children, the placebo group - 15 children. Initially, intestinal colics were noted in 21 (70%) children from the main group, and in 11 (73%) - from the control group. After multi-strain probiotic intake, intestinal colics kept in 3 (10%) children from the main group, and in all children from the placebo group. At the baseline, posseting was noted in 1/3 of children from the main group and in 3 (20%) patients in the placebo group. After 2 weeks posseting occurred only in 3 (10%) children from the main group. In the placebo group the posseting frequency did not change. After probiotic intake, 24 (80%) children had semi-liquid feces, in the placebo group stool disorders (loose stool, watery diarrhea or constipation with the need of voiding after enema) were reported in 13 (87%) children. While intaking the multi-strain probiotic, a tendency to restore the activity of the obligate colonic microflora, to reduce the activity of facultative and residual anaerobic and aerobic microflora was noted.Conclusion: The multi-strain probiotic can be recommended as a preparation of correction of functional disorders of the GIT and metabolic activity of the intestinal microflora in infants.